NEWS FROM MT. DUSHAK-EREKDAG STATION OF ODESSA ASTRONOMICAL OBSERVATORY - Dorokhov, N. I.; Dorokhova, T. N.; Komarov, N. S.; Mukhamednazarov, S. (Одеські астрономічні публікації, 2017)
This report continues the series of articles about observations at the Mt. Dushak-Erekdag station of Astronomical Observatory, Odessa State University in Turkmenistan. A 0.8 m telescope with the dualchannel PMT photometer is installed at the station. From 1993 to 1997 years the photometer participated in 6 asteroseismological campaigns and in some international programs. The instrumentation is modernized and quality of observations is improved. The following scientific researches are carried out at the station: ro (rapidly oscillating) Ap, δ Scuti and λ Booti stars, variability in the spots of cool stars, close binary systems, etc. Besides the station participated in the programs of asteroids, security and investigations of Solar system by means of photometric observations of eclipses and occultations of large planets, satellites. This work became possible thanks to cooperation with colleagues from different countries.